Deposition and characterization of silver nano-films by a novel solid liquid interface reaction technique (SLIRT) - Godbole, P. D.; Mitra, A.; Pasricha, R.; Mandale, A. B.; Patil, K. R. (Materials Letters, 2005)
Solid-liquid interface reaction technique (SLIRT) is used to deposit silver film on glass substrate. The solid film of silver nitrate is formed by modified spin coating method. This film is subsequently processed by dipping it in a reducing solution so as to initiate a reaction at the interface and ultimately transform it to totally silver film. In situ transformation of silver nitrate to silver is studied with respect to time spectrophotometrically. The characterization of silver film is done by various physicochemical techniques namely XRD, XPS, ED, TEM and UV visible spectroscopy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Nano-Particles; solid-liquid interface reaction; thin film

Densities and heat capacities of the ammonia plus water plus NaOH and ammonia plus water plus KOH solutions - Salavera, D.; Libotean, S.; Patil, K. R.; Esteve, X.; Coronas, Alberto (Journal of Chemical and Engineering Data, 2006)
Ammonia + water + sodium hydroxide and ammonia + water + potassium hydroxide mixtures were chosen as potential candidates for absorption chillers driven by low-temperature heat sources. Heat capacity and density were studied between (293.15 and 353.15) K at a constant pressure of 1.8 MPa for these solutions using a heat flux Calvet-type calorimeter and a vibrating-tube densimeter, respectively. Measured data were well-correlated with temperature and composition using simple polynomial equations. The relative deviations between the experimental and calculated values in the density and heat capacity measurements were 0.20 % and 0.49 % for NH3 + H2O + NaOH solutions and 0.10 % and 0.36 % for NH3 + H2O + KOH solutions, respectively. Also, two density prediction methods were checked using the experimental data. Previously, it was necessary to measure the density of ammonia and hydroxide aqueous solutions in similar conditions. The results showed that both methods are suitable for predicting the density of these solutions.

Direct synthesis of nanocrystalline silver from the reaction between silver carboxylates and n-trioctylphosphine - Charan, Shobhit; Singh, Narendra; Khanna, P. K.; Patil, K. R. (Journal of Nanoscience and Nanotechnology, 2006)
Neat n-Trioctylphosphine (TOP) has been used for the first ever time for reduction of silver nitrate and silver carboxylates (citrate, oleate, and myristate) under mild thermal reaction conditions. UV-visible absorption measurements of re-dispersible silver particles that were obtained by reduction of silver myristrate (product-IV) and silver nitrate (product-I) showed surface plasmon resonance absorption peak at 400 nm. The powder XRD pattern of fcc zero-valent silver resulted in diameters in the range of about 25-30 nm. TEM analysis showed particle diameter similar to that was observed by the XRD. FTIR spectroscopy revealed that the organics from the carboxylate group are retained by the nano-particles in case of product-IV however, presence of TOP is observed in product-I. It is found that when silver nitrate is reduced by TOP, spherical silver nano-particles with poor redispersity are formed but extended heating results in formation of long silver rods of micrometer size however, the re-dispersible nano-particles are easily formed when silver carboxylates are reduced by TOP.
Keywords: Chemical synthesis; Nanocrystalline; noble metal; XRD

Degradation of methylene blue via photocatalysis of transition metal-loaded sulfated TiO2 - Gambhire, A. B.; Lande, Machhindra K.; Arbad, B. R.; Rathod, S. B.; Gholap, Ramkrishna S.; Patil, K. R. (Materials Chemistry and Physics, 2011)
Transition metal-loaded nanocrystalline SO42-/TiO2 powders were prepared by sol-gel method. Anatase is found as the active phase in all the samples. Sulfation process clearly stabilizes TiO2 catalyst phase against sintering, maintaining anatase phase and relatively high surface area values with respect to pure TiO2. Wide structural and surface characterization of samples was carried out in order to establish a correlation between the effect of sulfation and metal incorporation on the TiO2 photocatalytic properties. The maximum photocatalytic decomposition of methylene blue solution was achieved with sulfation of TiO2. In addition, incorporation of metal into the structure of SO42-/TiO2 seems to enhance the photocatalytic activity of the samples, which is ascribed to the enlargement of specific surface area, photogenerated carriers separation, light absorption, as well as the higher surface acidity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: nanomaterial; Photocatalytic activity; sol-gel process